Safe Bets or Hot Hands? How Status and Celebrity Influence Strategic Alliance Formations by Newly Public Firms - Hubbard, Timothy D.; Pollock, Timothy G.; Pfarrer, Michael D.; Rindova, Violina P. (Academy of Management Journal, 2018)
Social approval assets derive their value from favorable stakeholder perceptions. Past research has focused primarily on their role as signals that reduce stakeholders’ perceived uncertainty about the firm. However, social approval assets can also serve as frames that influence how other information is interpreted. We theorize how the frames associated with two social approval assets—status and celebrity—influence the interpretation of equivocal information about newly public firms. Specifically, we examine how each frame influences the way underpricing is interpreted, and how these interpretations, as well as the joint effects of possessing status and celebrity, influence newly public firms’ strategic alliance formations. We explore these ideas in the ambiguity-ridden context of “Dot-Com” firms during the commercial dawn of the Internet. Our findings generally support our arguments, providing new theory and evidence about the framing effects of social approval assets with different sociocognitive content, and the dynamics of information and frame (in)congruence.